Patient tracking during treatment of children with cancer in India – An exploratory study. Issue 6 (23rd February 2021) - Ahuja, S; Sharma, J; Gupta, S; Bakhshi, S; Seth, R; Singh, A; Bagai, P; Arora, RS
Abstract: Background: Abandonment of treatment, a major cause of treatment failure in low‐ and middle‐income countries like India, is particularly high during the diagnostic and initial phase of treatment. Tracking of patients during this risk period may reduce treatment abandonment rates and increase quality of care. Aim: The primary aim was to pilot the use and check the acceptability of a tool for tracking children with cancer in New Delhi during the initial part of their treatment. Secondary aim was to estimate abandonment rates among these patients. Methods: This prospective study was carried out in two centers of North India in New Delhi and enrolled children less than 18 years diagnosed with cancer at these centers and who had registered with Cankids for social support. Parent support group (PSG) workers maintained contact with the child's family at least once a week for the first 12 weeks. Details of each contact and subsequent action were recorded in a customized book (called "You are not alone" or YANA Book). Descriptive analysis of these contacts was done in Microsoft Excel and presented in frequencies and percentages. The five‐point Likert scale was used to check the acceptability of the tool among the PSG workers. Results: Seven PSG workers enrolled and tracked 81 patients (73% male with a median age of 6 years). During the 12‐week study period, 986 contacts were attempted and three (3.7%) patients had abandoned their treatment. All PSG workers strongly agreed that the YANA book was simple to understand and use, decreased their workload, and helped provide better assistance to patients. Conclusion: The tool for patient tracking was well accepted by the PSG workers and considered easy to use. We now plan to implement our model as a routine service at all the partnering hospitals in India.